An audit and reaudit of the management of shoulder dystocia: an incomplete audit cycle. (16th November 2010) - Hamouda, T; Giamougiannis, P; Toeima, E; Fraser, D
Abstract : Introduction: Shoulder dystocia is a common and unpredictable complication of vaginal delivery affecting 1 in 300–500 deliveries. Good management of the delivery minimises the risk of trauma. Comparison between two audits First audit Second reaudit Year 2nd half 2007 2nd half 2008 Number of notes audited 38 48 Call for help 22/38 (58%) 27/48 (56%) Suprapubic pressure 17/38 (47%) 20/48 (41%) Mc Roberts 37/38 (97%) 45/48 (93%) Episiotomy 16/38 (42%) 18/48 (37%) pH 25/38 (65%) 32/48 (66%) Anterior Shoulder 03/38 (07%) 08/48 (16%) Incident form 10/38 (26%) 17/48 (35%) Paeds attended 13/38 (34%) 22/48 (45%) Emergency chart filled 05/48 (10% Aim: The management of shoulder dystocia was audited during 2007 and reaudited in 2008 to ensure that it complies with Trust and Royal College of Obstetricians and Gynaecologists guidelines and to complete the audit cycle. In the first audit the authors advised 100% compliance with standards and to use the emergency chart for shoulder dystocia. Comments: There was little difference in most of the results when compared with the previous audit. The emergency chart was used only in five cases. There was some improvement in documenting which shoulder was anterior. Generally the authors are performing significantly worse than the target (100%). Recommendations: To make medical and midwifery staff aware of the importance of using the emergency chart in all cases labelled as having shoulder dystocia. Reaudit on the management of shoulder dystacia by the end of 2010.